The Moderation Effect of Technology Anxiety on Digital Transformation Readiness in Public Universities: An Organizational Readiness Approach - Patabang, Mety; Dedi Iskandar Inan; Amestina Matualage; Indra, Muhamad (JUSIFO : Jurnal Sistem Informasi, 2024)
The transition toward digital transformation in higher education institutions is imperative for enhancing efficiency, transparency, and sustainability. This study evaluates the digital transformation readiness of administrative personnel at the University of Papua, focusing on organizational readiness factors: resource availability, cultural adaptability, and ICT infrastructure. The moderating role of technology anxiety, alongside demographic factors such as age and gender, was also analyzed to understand their influence on the institution's preparedness for digitalization. Findings reveal significant associations between readiness components and the ability to effectively adopt digital technologies, while technology anxiety was found to moderate these relationships. The study underscores the critical need for addressing environmental concerns, including paper waste, by implementing sustainable digital practices. Through robust statistical methods and an organizational readiness framework, this research provides actionable insights for institutions aiming to navigate the complexities of digital transformation successfully.